Evaluation of speed and reaction time of upper members in basketball athletes in wheelchair (Research, Society and Development, 2020)
Objective: To validate the speed and reaction time of the senior members of the basketball team in the wheelchair of the city of Guarapuava-PR. Methodology: Using the plate strike test and the test. Both modified the tests were for rhodes chair. A program was composed of ten individuals who showed heterogeneity in training time and types of disabilities. Results: The ruler test showed an average of 0.18s without reaction time, which is considered very low compared to other studies. Do not test the agitation of the plate, as a means of 22.43s has been found. Compared to other works that will use this protocol, athletes will have an inferior performance. Conclusion: Athletes have a good reaction time and, therefore, present scores much lower than expected in reaction speed.